β-Elemene Reverses the Resistance of p53-Deficient Colorectal Cancer Cells to 5-Fluorouracil by Inducing Pro-death Autophagy and Cyclin D3-Dependent Cycle Arrest - Zhang, Ruonan; Pan, Ting; Xiang, Yu; Zhang, Mingming; Feng, Jiao; Liu, Shuiping; Duan, Ting; Chen, Peng; Zhai, Bingtao; Chen, Xiaying; Wang, Wengang; Chen, Bi; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: Colorectal cancer is the third most common cancer worldwide and the second most common cancer cause of death worldwide. 5-fluorouracil remains a widely used chemotherapeutic drug in the treatment of advanced colorectal cancer, but chemotherapy drugs are prone to drug resistance, p53 deletion or mutation is an important reason for the resistance of colorectal cancer cells to 5-fluorouracil. β-elemene has been proved to have the potential of reverse chemotherapy drug resistance, but the mechanism is unknown. This study aimed to investigate the effect of β-elemene to 5-fluorouracil in drug-resistant p53-deficient colorectal cancer cells HCT116p53-/-, and determine the possible molecular mechanism of β-elemene to reverse 5-fluorouracil resistance. Methods: The effect of β-elemene on HCT116p53-/- cell activity was detected by Cell counting Kit-8. Cell proliferation was detected by monoclonal plate. The apoptosis was detected by flow cytometry and western blot. The autophagy was detected by western blot, immunofluorescence and transmission electron microscope. Determine the role of Cyclin-related protein Cyclin D3 in β-elemene reversing the resistance of HCT116p53-/- to 5-fluorouracil was detected by overexpression of Cyclin D3. The effect of β-elemene on the tumorigenic ability of p53-deficient colorectal cancer cells was detected establishing HCT116p53-/- all line xenograft model. Results: For p53 wildtype colorectal cancer cells, β-elemene could augment the sensitivity of 5-fluorouracil, for p53-deficient colorectal cancer cells, β-elemene significantly inhibited cell proliferation in a concentration-dependent manner, and reverse the resistance of HCT116p53-/- to 5-fluorouracil by inducing pro-death autophagy and Cyclin D3-dependent cycle arrest. Conclusion: β-elemene enhances the sensitivity of p53 wild-type cells to 5-fluorouracil, β-elemene can reverse the resistance of HCT116p53-/- to 5-fluorouracil by inducing pro-death autophagy and Cyclin D3-dependent cycle arrest in p53-deficient colorectal cancer，which will provide a new method for the treatment of p53 deletion colorectal cancer patients.